2000
DOI: 10.1080/00288233.2000.9513452
|View full text |Cite
|
Sign up to set email alerts
|

Microbial pathogens and plant parasitic nematodes in pastures with declining vigour

Abstract: Two years after establishment, areas of low vigour (LV) were noticed within a white clover (Trifolium repens)/ryegrass (Lolium perenne) pasture. These areas became progressively larger, and, two years later, the pasture had low vigour, comprising only 3% white clover. Clover tissue nitrogen and phosphorus levels were greater in high vigour (HV) than in LV herbage. There were no differences (P > 0.05) in "total" bacteria, fluorescent pseudomonads, or proportions of deleterious bacteria in LV and HV white clover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…These include nematodes, fungi, and Oomycetes (Falloon 1985;Skipp and Christensen 1989;Waipara et al 1996;Watson and Mercer 2000;Sarathchandra et al 2000), which vary from highly host-specific through to broad-range generalists. In most cases, however, root diseases are often caused by a suite (disease complex) of pathogens (Skipp and Watson 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include nematodes, fungi, and Oomycetes (Falloon 1985;Skipp and Christensen 1989;Waipara et al 1996;Watson and Mercer 2000;Sarathchandra et al 2000), which vary from highly host-specific through to broad-range generalists. In most cases, however, root diseases are often caused by a suite (disease complex) of pathogens (Skipp and Watson 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, the bulk of research efforts were conducted in the mid 1980's through to the early 2000's (Falloon 1985;Skipp and Christensen 1989;Waipara et al 1996;Watson and Mercer 2000;Sarathchandra et al 2000), with relatively little work conducted for the past 15 years. This is at odds with the trend for increased value of pasture production on a per hectare basis.…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, soil-borne pathogens commonly-associated with diseases of grass and forage legume seedlings include Rhizoctonia solani (Kuhn), Pythium ultimum (Trow) (Skipp & Watson, 1996) and Sclerotinia trifoliorum Eriks (Skipp & Hampton, 1996). R. solani and P. ultimum can reduce establishment of grasses and legumes (Skipp & Christensen 1989a,b;Waipara et al,1996;Sarathchandra et al, 2000). In perennial ryegrass (Lolium perenne L.) these pathogens usually infect the seed or seedling prior to emergence (preemergence damping off -Falloon, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The individual genera of plant feeding nematodes listed in Table 3 are in order of their potential to damage pasture plants so that the high population levels of root knot (range 0-5459 × 10 3 /m 2 ) and cyst nematodes (0-509 × 10 3 /m 2 ) observed in some paddocks is likely to be of concern. As is the case for grass grub, these nematodes can increase rapidly in the first 2 to 3 years after establishment of new pasture (Sarathchandra et al 2000), even after cropping has been used to remove plant hosts as Watson et al (2000) found at a Bay of Plenty site. Some of the variables measured were significantly (P<0.05, n=24) correlated with each other.…”
Section: Resultsmentioning
confidence: 99%